Analysis Of Factors Influencing Employee Retention: A Study On Start-Up Companies In The Information Technology Sector - Darmayanti Darmayanti; Badia Perizade; Isnurhadi Isnurhadi; Yuliani Yuliani (Eduvest - Journal of Universal Studies, 2024)
The current digital era, start-up companies in the information technology (IT) sector face challenges in retaining quality employees. Employee retention is crucial because a company's success depends on their ability to retain top talent. However, high employee turnover rates can disrupt operational consistency and long-term growth. The aim of this research is to analyze the factors that influence employee retention in start-up companies in the information technology sector. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that the factors that influence employee retention in startup companies in the information technology sector are very important because valuable and competent employees are the main asset in creating and maintaining a company's competitive advantage. Factors that influence employee retention include employee engagement, communication, compensation, leadership, career development, training and development, work flexibility, job satisfaction, and performance appraisal.